Analisis Pendapatan Usahatani Pisang Klutuk di Desa Puhu Kecamatan Payangan Kabupaten Gianyar - JESICA AGUSTIN; I GUSTI AGUNG AYU AMBARAWATI; I WAYAN BUDIASA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Income Analysis of Klutuk Bananas at Puhu Village Payangan District Gianyar Regency This study aims to determine costs used, revenue and income of klutuk banana farming. The location of the research was determined purposively at Puhu Village, Payangan District, Gianyar Regency. The population in this study was klutuk banana farmers at Puhu Village, Payangan District, Gianyar Regency. The sampling technique used was purposive sampling method. Samples in this study were 55 respondents of farmers determined by using Slovin method. This research uses descriptive quantitative and qualitative to calculate income of klutuk banana cultivation at Puhu Village. The results of this study show that average farm income received by farmers was Rp 3,503,207 in the first year and in the second year at amount Rp 4,401,317. Technical obstacles experienced by farmers on klutuk banana farming at Puhu Village were the existence of green grasshopper and strong wind. Hindrance from the economic point of view was price fluctuations between wet and dry seasons.